The distortionary effects of sterilised reserve accumulation on domestic credit markets: Evidence from Uganda - Jimmy ApaaOkello; Beatrice K. Mkenda; Eliab Luvanda (Central Bank Review (CBR), 2019)
Some small open Least Income Countries embarked on rapid accumulation of foreign reserves in the wake of volatile capital inflows. Foreign reserve accumulation is one way of managing volatile capital flows. However, rapid and persistent accumulation is not only costly, but potentially distort the domestic financial markets, especially when it is financed by sterilisation. This study investigates the potential distortions on commercial bank lending in Uganda. Our empirical results show that sterilised reserve purchases crowd-out bank lending. The crowding-out effect is persistent even when bank capitalisation and shifts in monetary policy regimes are controlled for, which raise important policy implications. The objective of sterilisation is to maintain the prevailing stance of monetary policy. However, when it alters the prevailing stance of monetary policy and consequently the direction of the impact of policy as the empirical result has shown, then sterilised reserve purchases violate the "impossible trinity" i.e. it weakens the monetary authority's control over domestic monetary conditions.
Keywords: E44; E52; E58; G21; 330; Sterilisation instruments; Crowd-out; Reserve accumulation; Least income countries; Uganda; Trilemma; Impossible trinity; Pooled mean group estimator